Effects of perceived change of urban destination on destination attachment - Huang, Mei; Yang, Xiaojie; Liu, Danping; Fang, Hedan (Frontiers in Psychology, 2022)
The impact of urbanization on tourism is a widespread macroeconomic concern. However, few studies have explored the impact of destination urbanization on such individual tourist behavior as destination attachment. By developing an urbanization perception scale and analyzing tourists’ destination attachment, this study provides empirical evidence for the micro-impact of urbanization. A sample of 825 repeat visitors of Chengdu, China, was included in the partial least squares-based structural modeling. The results of several tests show that the environmental changes caused by green urbanization positively impact tourists’ destination attachment. This study also examines the explanatory role of tourist experience satisfaction and behavior control in this relationship. The findings suggest that tourists’ experience of urban change is critical for the sticky marketing of tourist destinations.